Nazewnictwo terenowe związane z motywami krajobrazowymi we wsiach wschodniej części dolnych Łużyc = Topographic nomenclature connected with landscape motives in the villages of eastern parts of lower lusatia till 1945 - Łachowska, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article addresses historical, geo-linguistic, and onomastic issues. As the gathered sources show, Slavic topographic names were common and widely used in the villages of eastern parts of Lower Lusatia. They were saved through the writings of the 19th century regionalists and explorers of the Silesian-Lusatian border area. Most of them testify to the usage of the Lower Sorbian language in the villages of the discussed region till 1945.
Keywords: Serbołużyczanie; onomastyka; motywy roślinne; Łużyce Wschodnie; Lusatians; onomastics; floral motifs; Eastern Lusatia; customs